2016
DOI: 10.3126/jcmsn.v12i3.15487
|View full text |Cite
|
Sign up to set email alerts
|

Association between Severity of Tooth Wear and Dentinal Hypersensitivity

Abstract: Background & Objectives: Tooth wear (attrition, abrasion, erosion, and abfraction) is perceived globally as ever increasing problem. Several outcome of the tooth wear are hypersensitivity, esthetic problems, functional impairment, annoyance to the patient, and fracture of the tooth. Among these, the measurable and more commonly reported outcome is hypersensitivity to stimuli. Although dentin hypersensitivity is a common clinical condition and is generally reported by the patient after experiencing a sharp,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Association between severity of tooth wear and cervical DH is still a scarce in the literature. Some studies found a positive correlation 21,22,23 . Reasons could be the proximity of the lesion with the pulp, the amount of exposed dentinal tubules and theory that root exposition makes the tissue more vulnerable to the influence of risk factors 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Association between severity of tooth wear and cervical DH is still a scarce in the literature. Some studies found a positive correlation 21,22,23 . Reasons could be the proximity of the lesion with the pulp, the amount of exposed dentinal tubules and theory that root exposition makes the tissue more vulnerable to the influence of risk factors 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Deshpande S 29 in a study reported that there is a connection between grades of tooth wear with dentin sensitivity. Ayer A et al 30 in a study reported that dentin hypersensitivity is associated with tooth surface loss. Idon P et al 31 in a study reported an association of dentin hypersensitivity with tooth surface loss.…”
Section: Discussionmentioning
confidence: 99%
“…7 Scores of 0-4 for the enamel and 0-5 for the dentine were assigned to the teeth, according to the severity of wear. 8 Statistical Methods: Collected data was entered in Microsoft Excel and coded accordingly. The statistical analysis was performed by statistical package for social science (SPSS).…”
Section: Samplingmentioning
confidence: 99%